KOMUNIKASI INSTRUKSIONAL GURU DALAM PROSES MENGAJAR SISWA AUTIS DI SLB PANAM MULIA PEKANBARU - Moenix Philberta Valentina; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Autism is a developmental disorder that involves cognitive, communication and social interaction problems. The term autism until now there are still many people who do not know well what is meant by people with autism, so that people with autism are often considered to have no abilities. To get rid of this stigma, autistic children are sent to special schools. The interaction carried out at the school is one of the processes of interaction between teachers and autistic students to meet the needs of these students. The purpose of this study was to see how the interaction between teachers and autistic students in applying the messages the teacher gave to these autistic students.This study used qualitative research methods. This research was conducted at the Panam Mulia Special School, Pekanbaru. The selection of informants was carried out using a purposive technique. Data collection techniques consisted of observation, interviews, and documentation. While data analysis techniques using descriptive analysis according to Huberman and Miles. For technique checking the validity of the data used in this study are participation extension and triangulation.The results of the study found that instructional communication between teachers and autistic students in the learning process was quite effective, at the time of the learning process teachers used nonverbal language more than their verbal language. The methods used in teaching are also quite effective. Then there are three types of obstacles, namely at the source, namely from the communicator, such as the use of complex language, obstacles in the channel, namely damaged equipment and unsupportive weather so that the learning atmosphere is disturbed. Instructional communication by the teacher has a positive impact on the social development of autistic students. Keywords: Komunikasi instruksional, Guru, Autis